Hypermethylation at 45S rDNA promoter in cancers. - Trang Thi Quynh Tran; Trang Hien Do; Tung The Pham; Phương Thi Thu Luu; Oanh Minh Pham; Uyen Quynh Nguyen; Linh Dieu Vuong; Quang Ngoc Nguyen; Tuan Van Mai; Son Van Ho; Than Thi Nguyen; Lan Thi Thuong Vo (PLoS ONE)
The ribosomal genes (rDNA genes) encode 47S rRNA which accounts for up to 80% of all cellular RNA. At any given time, no more than 50% of rDNA genes are actively transcribed, and the other half is silent by forming heterochromatin structures through DNA methylation. In cancer cells, upregulation of ribosome biogenesis has been recognized as a hallmark feature, thus, the reduced methylation of rDNA promoter has been thought to support conformational changes of chromatin accessibility and the subsequent increase in rDNA transcription. However, an increase in the heterochromatin state through rDNA hypermethylation can be a protective mechanism teetering on the brink of a threshold where cancer cells rarely successfully proliferate. Hence, clarifying hypo- or hypermethylation of rDNA will unravel its additional cellular functions, including organization of genome architecture and regulation of gene expression, in response to growth signaling, cellular stressors, and carcinogenesis. Using the bisulfite-based quantitative real-time methylation-specific PCR (qMSP) method after ensuring unbiased amplification and complete bisulfite conversion of the minuscule DNA amount of 1 ng, we established that the rDNA promoter was significantly hypermethylated in 107 breast, 65 lung, and 135 colon tumour tissue samples (46.81%, 51.02% and 96.60%, respectively) as compared with their corresponding adjacent normal samples (26.84%, 38.26% and 77.52%, respectively; p < 0.0001). An excessive DNA input of 1 μg resulted in double-stranded rDNA remaining unconverted even after bisulfite conversion, hence the dramatic drop in the single-stranded DNA that strictly required for bisulfite conversion, and leading to an underestimation of rDNA promoter methylation, in other words, a faulty hypomethylation status of the rDNA promoter. Our results are in line with the hypothesis that an increase in rDNA methylation is a natural pathway protecting rDNA repeats that are extremely sensitive to DNA damage in cancer cells.